11m+13=m+12

Simple and best practice solution for 11m+13=m+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11m+13=m+12 equation:


Simplifying
11m + 13 = m + 12

Reorder the terms:
13 + 11m = m + 12

Reorder the terms:
13 + 11m = 12 + m

Solving
13 + 11m = 12 + m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-1m' to each side of the equation.
13 + 11m + -1m = 12 + m + -1m

Combine like terms: 11m + -1m = 10m
13 + 10m = 12 + m + -1m

Combine like terms: m + -1m = 0
13 + 10m = 12 + 0
13 + 10m = 12

Add '-13' to each side of the equation.
13 + -13 + 10m = 12 + -13

Combine like terms: 13 + -13 = 0
0 + 10m = 12 + -13
10m = 12 + -13

Combine like terms: 12 + -13 = -1
10m = -1

Divide each side by '10'.
m = -0.1

Simplifying
m = -0.1

See similar equations:

| 3x^2+11x=2 | | 12x-3y+5x+5y= | | x^2-19x-56=0 | | 19y=18(y+6) | | 2x+3x-8+9=5x-x+12-8 | | -z^2= | | -5+13=16x-3-15x | | (9+u)(5u+2)=0 | | -3v+7v-v= | | x-0.2x=0.8 | | x+5.2=6.8+2(x-0.2) | | (z+8)(z+1)=0 | | x-(-7-3x)=-5 | | (z+8)(2+1)=0 | | x-0.2x=135.72 | | x-7-3x=-5 | | 0.2b-3=0.7+1.5 | | -2x+3=9 | | -6n+9=-5n-19 | | 8(3x-5)=4(6x+3) | | 8x+6-9x=2 | | 3x+2x+5=4x-2 | | (1-w)(3w-5)=0 | | -2x-3=-9 | | 3w-5=0 | | 14x-2=0 | | 3y=-5x+12 | | 9z=-45 | | 8x-4x+2=48 | | x^3-x^2-16=20 | | 8(3x-5)=(6x+3) | | 2Inx=4 |

Equations solver categories